2019
DOI: 10.1101/853721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Push-to-open: The Gating Mechanism of the Tethered Mechanosensitive Ion Channel NompC

Abstract: NompC was one of the earliest identified mechanosensitive ion channels responsible for the sensation of touch and balance in Drosophila melanogaster. A tethered gating model was proposed for NompC and the Cryo-EM structure has been solved. However, the atomistic mechano-gating mechanism still remains elusive. Here we show the atomistic details of the NompC channel opening in response to the compression of the intracellular domain while remaining closed under an intracellular stretch. This is demonstrated by al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…In our study, we provide in vitro evidence for the first example of a membrane β-barrel protein that exhibits membrane state-dependent mechanosensitive-like properties. Our findings are consistent with the "tether model" 33 , where an intermembrane protein anchor domain (here Tom22) limits lateral diffusion, as observed for a large number of α-helical membrane proteins 32,33,[38][39][40][41] . It will be interesting to study whether the in vitro properties of the TOM-CC can be confirmed in intact mitochondria.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we provide in vitro evidence for the first example of a membrane β-barrel protein that exhibits membrane state-dependent mechanosensitive-like properties. Our findings are consistent with the "tether model" 33 , where an intermembrane protein anchor domain (here Tom22) limits lateral diffusion, as observed for a large number of α-helical membrane proteins 32,33,[38][39][40][41] . It will be interesting to study whether the in vitro properties of the TOM-CC can be confirmed in intact mitochondria.…”
Section: Discussionsupporting
confidence: 89%
“…Mechanosensitivity via force transmission from a tether to the extracellular matrix and/or the cytoskeleton has been established for a number of -helical membrane proteins (Brohawn et al, 2014a(Brohawn et al, , 2014bGe et al, 2018;Jin et al, 2020;Kefauver et al, 2020;Martinac, 2004;Pliotas and Naismith, 2017;Teng et al, 2015;Yang Wang et al, 2019). These findings go along with our observations for the TOM-CC, which seems to obey the "tether model" proposed by Kefauver et al (2020) (Kefauver et al, 2020), where an intermembrane protein anchor domain limits lateral diffusion.…”
Section: Discussionsupporting
confidence: 85%
“…Atomic force microscopy measurements had previously shown that isolated NOMPC ARD acts analogously to a linear and fully reversible spring 111 . Molecular dynamics simulations using the NOMPC structure show that compression of the ARDs can produce a clockwise movement of the TRP domain and linker helices, similar to the TRPV1 closed-to-open gating transition 28,112 (Fig. 2e).…”
Section: Transient Receptor Potential Channelsmentioning
confidence: 93%
“…Force is transmitted to the channel via a tether to the extracellular matrix, the cytoskeleton or both. For example, NOMPC (middle) is tethered to microtubules via its ankyrin repeat domain (emerald) 112 . Right, the MET channel complex is tethered to the neighbouring stereocilium via the tip link (PCDH15; emerald) 16 .…”
mentioning
confidence: 99%